Polyamine Oxidase 5 (PAO5) mediated antioxidant response to promote salt tolerance in Arabidopsis thaliana - Nur-E-Ferdousy; Tahjib-Ul-Arif, Md.; Sagor, G. H. M. (Journal of the Bangladesh Agricultural University, 2024)
Polyamines are aliphatic polycations ubiquitously found in plants, involved in growth, development and many other physiological processes. Polyamine oxidases are monomeric proteins of about 55 kDa that bear a non-covalently bound molecule of FAD as a cofactor which are responsible for polyamines catabolism. They play very crucial role in polyamine homeostasis. The present study was executed to know the physiological role of polyamine oxidases by using five polyamine oxidase mutants namely pao1, pao2, pao3, pao4, pao5 along with wild type Col-0. There was almost no difference at physiological condition, but the profound difference was found under salt stress condition. Among the plants pao5 mutants which is known to have two times higher thermospermine (T-Spm) content exhibited the maximum tolerance under salt stress compared to Col-0 and other mutants. The phenomenon was also confirmed using PAO5 promoter::GUS transgenic plants. At physiological condition, PAO5 promoter activity was observed throughout the plant but intensity is very low, likely, the intensity started to increase gradually once exposed to salt stress and after 9 hours the intensity was very high. Then to reveal the underlying mechanism of stress tolerance, ROS accumulation and antioxidant enzyme activity in pao5 mutants were measured. Atpao5 showed almost lower level of ROS accumulation and higher level of antioxidant enzyme activity both in salt stress and control compare to wild type plants. Thus, indicated that lack of AtPAO5 gene has crucial role in stress tolerance through maintaining the level of T-Spm in Arabidopsis thaliana. J Bangladesh Agril Univ 18(2): 203–211, 2020 https://doi.org/10.5455/JBAU.103110